Effects of Gas Rarefaction on Used Nuclear Fuel Cladding Temperatures during Vacuum Drying. (1st June 2016) - Hadj-Nacer, M.; Manzo, T.; Ho, M. T.; Graur, I.; Greiner, M.
Abstract: A two-dimensional computational model of a loaded used nuclear fuel canister filled with dry helium gas was constructed to predict the cladding temperature during vacuum-drying conditions. The model includes distinct regions for the fuel pellets, cladding, and helium within each basket opening, and it calculates the conduction heat transfer within all solid components, heat generation within the fuel pellets, and conduction and surface-to-surface radiation across the gas-filled regions. First, steady-state simulations are performed to determine peak clad temperatures as a function of the fuel heat generation rate, assuming the canister is filled with atmospheric pressure helium. The allowable fuel heat generation rate, which brings the peak clad temperature to its limit, is evaluated. The discrete velocity method is then used to calculate slip-regime rarefied gas conduction across planar and cylindrical helium-filled gaps. These results are used to verify the Lin-Willis solid-gas interface thermal resistance model for a range of thermal accommodation coefficients α. The Lin-Willis model is then implemented at the solid-gas interfaces within the canister model. Finally, canister simulations with helium pressures of 100 and 400 Pa and α = 1, 0.4, and 0.2 are performed to determine how much hotter the fuel cladding is under vacuum-drying conditions compared to atmospheric pressure. For α = 0.4, the fuel heat generation rates that bring the clad temperature to its allowed limit for helium pressures of 400 and 100 Pa are reduced by 10% and 25%, respectively, compared to atmospheric pressure conditions. Transient simulations show that the cladding reaches its steady-state temperatures ~20 to 30 h after water is removed from the canister.